2016
DOI: 10.1126/science.aaf1288
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Multiple repressive mechanisms in the hippocampus during memory formation”

Abstract: Cho et al. (Reports, 02 October, p.82) report that gene repression following contextual fear conditioning regulates hippocampal memory formation. We observe low levels of expression for many of the top candidate genes in the hippocampus, and robust expression in choroid plexus, as well as repression at 4 hours following contextual fear conditioning, suggesting the inclusion of choroid plexus mRNAs in Cho et al. hippocampal samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Interplay between CSF Composition and Brain Function in the Context of Stress, Disease, and Neurodevelopmental Disorders Following stress induced by contextual fear conditioning, expression of ChP genes is dramatically suppressed, in some cases to a greater degree than in the adjacent hippocampus (Cho et al, 2015;Mathew et al, 2016). Such changes have the potential to alter learning and memory via differential exchange of blood-borne signals between the CSF, removal of other signals, as well as changes in ChP secretion of plasticity-related signals into the CSF.…”
Section: Development Of Chp Immune Functionsmentioning
confidence: 99%
“…Interplay between CSF Composition and Brain Function in the Context of Stress, Disease, and Neurodevelopmental Disorders Following stress induced by contextual fear conditioning, expression of ChP genes is dramatically suppressed, in some cases to a greater degree than in the adjacent hippocampus (Cho et al, 2015;Mathew et al, 2016). Such changes have the potential to alter learning and memory via differential exchange of blood-borne signals between the CSF, removal of other signals, as well as changes in ChP secretion of plasticity-related signals into the CSF.…”
Section: Development Of Chp Immune Functionsmentioning
confidence: 99%
“…It is noteworthy that it has been recently reported that the CP might be, at least partially, involved in the contextual fear-learning as it exhibits, in some instances, stronger response to stressful stimuli at the levels of gene transcription as compared to the hippocampus. Altered expression of multiple genes encoding secreted molecules such as the putative hormone augurin represent an example [72,73]. Recently, the CP has been also implicated as an entry site for various hormones produced in response to changed physiological state that are present in the blood, thus directly affecting their availability in the brain.…”
Section: The Choroid Plexus-key Regulator Of Csf Productionmentioning
confidence: 99%
“…First, it enriches for cell type-specific translational changes, reducing the problem of heterogeneity of gene expression changes in response to a physiologically relevant stimulus. Second, TRiP improves reproducibility across samples as it is insensitive to imprecise dissection, a problem that can produce misleading results (Mathew et al 2016).…”
Section: Discussionmentioning
confidence: 99%